South Asia Economic Focus, Fall 2017 : Growth Out of the Blue - World Bank (Washington, DC: World Bank, 2017)
For eight consecutive quarters South Asia was the fastest-growing region in the world… but not anymore. Despite benign global conditions, regional growth has slowed down. This trend is the result of a deceleration in India, the region’s powerhouse. Short-term disruptions related to the introduction of the landmark Goods and Services Tax can explain the steep decline observed in the last quarter, but the deceleration has been going on for more than one year. Over this period imports increased sharply while private investment declined. Behind these trends lies a combination of large public sector borrowing (especially by the states), relatively sticky interest rates despite decreasing inflation, and an increasingly stressed financial sector. While growth has slightly accelerated elsewhere in the region, concerns remain. Bangladesh has seen an increase in financial sector risks and in Pakistan macroeconomic discipline has weakened.